Equipos ideales cómo reconocer y cultivar las tres virtudes esenciales - Lencioni, Patrick 1965-; Rodríguez Courel Ginzo, Martín (BookaVivo, 2021)
In Dream Teams, Lencioni tells the story of Jeff Shanley, a leader desperate to save his uncle's company by restoring cultural commitment to teamwork. Jeff has to crack the code of the strengths people on the team possess and then build a culture of hiring and development around those strengths. Beyond the fable, Lencioni presents a practical framework and tools for the identification of concrete actions, the hiring and the development of ideal personnel to work in a team. Whether you're a leader trying to create a culture of teamwork, or professional staffing looking to hire a real team, or a team person wanting to improve, you'll find this book both helpful and compelling.
Online resource; title from title details screen (O'Reilly, viewed May 18, 2022)
Keywords: Leadership; Teams in the workplace -- Management; Corporate culture; Équipes de travail; Gestion; Culture organisationnelle; Teams in the workplace; Management; Downloadable audio books; Audiobooks; Livres audio